The influence of the flat shape spin wheel learning media on mathematics learning to improve conceptual understanding of phase B Students at Khaira Ummah Islamic Elementary School - Yuliantika, Sonya; Frasandi, Rendy Nugaraha; Rahmatika, Ulva; Septiana, Nyangfah Nisa (Mitra PGMI: Jurnal Kependidikan MI, 2025)
This study stems from the problem of low student engagement in the mathematics learning process, which is often considered a difficult subject due to the infrequent use of interesting and supportive learning media by educators. In general, educators only rely on images found in textbooks or drawn on the blackboard, which has an impact on students' low understanding of concepts in the learning process. To address this issue, this study aims to examine the extent to which the use of the ROTAR (rotating wheel) learning media for flat shapes affects the improvement of concept understanding among phase B students at SD Islam Khaira Ummah. This study employs a quantitative approach using a quasi-experimental method and a pretest-posttest control group design. The sample in this study was determined using cluster random sampling, involving two classes: class IVB as the experimental group using the rotar media, and class IVC as the control group using conventional learning media. Data analysis results showed a significant increase in conceptual understanding in the experimental group, with an average increase of 32.64 points, higher than the control group, which only experienced an increase of 20.30 points. The t-test results showed a significant value (one-tailed) of 0.000 (< 0.05), indicating that the use of rotar media significantly influences the improvement of students' mathematical concept understanding. This finding recommends that educators utilize varied learning media to create a more engaging and meaningful learning environment.